Psychiatric and socioeconomic aspects as possible predictors of compulsive buying behavior - Priscilla Lourenço Leite; Adriana Cardoso Silva (Trends in Psychiatry and Psychotherapy)
Abstract Introduction: Compulsive buying can be characterized as an almost irresistible urge to buy various items. Compulsive buying disorder is a subject of growing interest to health professionals. It is a current issue and the prevalence rate in the global population is around 5 to 8%. Objectives: The main objective of this study was to identify predictors of compulsive buying in the Brazilian population, assessing possible relationships between compulsive buying, depression and anxiety. Methods: The Richmond Compulsive Buying Scale was administered to screen for compulsive buying and the Hospital Anxiety and Depression Scale was used to assess anxiety and depression in a sample of 359 participants. Pearson coefficients were used to test for correlations. Results: Our study identified an interaction between female gender and compulsion to purchase. Furthermore, people's occupations also appear to have an influence on the problem. We found a correlation between depressive symptoms and oniomania. Conclusion: Our study has certain limitations, such as the difficulty in recruiting individuals with compulsive buying disorder. Since compulsive buying is a phenomenon that is seldom investigated, it therefore remains unidentified. However, this is nevertheless a pioneering paper on the Brazilian population.